Tablet‐based electroencephalography diagnostics for patients with epilepsy in the West African Republic of Guinea. (30th May 2020) - Sokolov, E.; Abdoul Bachir, D. H.; Sakadi, F.; Williams, J.; Vogel, A. C.; Schaekermann, M.; Tassiou, N.; Bah, A. K.; Khatri, V.; Hotan, G. C.; Ayub, N.; Leung, E.; et al.
Abstract : Background and purpose: Epilepsy is most common in lower‐income settings where access to electroencephalography (EEG) is generally poor. A low‐cost tablet‐based EEG device may be valuable, but the quality and reproducibility of the EEG output are not established. Methods: Tablet‐based EEG was deployed in a heterogeneous epilepsy cohort in the Republic of Guinea (2018–2019), consisting of a tablet wirelessly connected to a 14‐electrode cap. Participants underwent EEG twice (EEG1 and EEG2), separated by a variable time interval. Recordings were scored remotely by experts in clinical neurophysiology as to data quality and clinical utility. Results: There were 149 participants (41% female; median age 17.9 years; 66.6% ≤21 years of age; mean seizures per month 5.7 ± SD 15.5). The mean duration of EEG1 was 53 ± 12.3 min and that of EEG2 was 29.6 ± 12.8 min. The mean quality scores of EEG1 and EEG2 were 6.4 [range, 1 (low) to 10 (high); both medians 7.0]. A total of 44 (29.5%) participants had epileptiform discharges (EDs) at EEG1 and 25 (16.8%) had EDs at EEG2. EDs were focal/multifocal (rather than generalized) in 70.1% of EEG1 and 72.5% of EEG2 interpretations. A total of 39 (26.2%) were recommended for neuroimaging after EEG1 and 22 (14.8%) after EEG2. Of participants without EDs at EEG1 ( n = 53, 55.8%), seven (13.2%) had EDs at EEG2. Of participants with detectable EDs on EEG1 ( n = 23, 24.2%), 12 (52.1%) did not have EDs at EEG2. Conclusions: Tablet‐based EEG had a reproducible quality level on repeat testing and was useful for the detection of EDs. The incremental yield of a second EEG in this setting was 13%. The need for neuroimaging access was evident.